(untitled) (PJDOL, 2023)
Effective student-teacher relationships lead to positive behavioral development of students. The purpose of this qualitative study was to investigate the influence of student-teacher relationships on the passiveaggressive behavior of students. A phenomenological research design was used to observe the classroom phenomena of two private sector schools that willingly agreed to participate in the study. Notes taken from twelve scheduled classroom observations, seven follow up interviews of selective students, and five teachers were used as sources of data.